2006
DOI: 10.1186/1471-2474-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and longitudinal construct validity of two rotator cuff disease-specific outcome measures

Abstract: Background: Disease-specific Quality Of Life (QOL) measures are devised to assess the impact of a specific disease across a spectrum of important domains of life. The purpose of this study was to examine the cross-sectional and longitudinal construct validity (sensitivity to change) of two rotator cuff diseasespecific measures, the Rotator Cuff-Quality Of Life (RC-QOL) and the Western Ontario Rotator Cuff (WORC) index, in relation to one another and to other joint and limb specific measures in the same populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 31 publications
2
92
1
1
Order By: Relevance
“…In addition, the advantage of rotator-cuff measures has not been proven to date in the shoulder-related literature. [19][20][21] Although the main value of the multiple-domain measures is in their ability to document the impact of disease on each QOL domain, we do not have supporting evidence for the specificity of information from each domain or sub-scale. 22,23 Several other shortcomings specific to the WORC can be noted.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, the advantage of rotator-cuff measures has not been proven to date in the shoulder-related literature. [19][20][21] Although the main value of the multiple-domain measures is in their ability to document the impact of disease on each QOL domain, we do not have supporting evidence for the specificity of information from each domain or sub-scale. 22,23 Several other shortcomings specific to the WORC can be noted.…”
mentioning
confidence: 96%
“…The ASES has been reported to be reliable 31 and valid 20,21,31,32 in patients with upper-extremity, shoulder, or rotator-cuff pathology. 10 The CMS combines a subjective component (35% of the total score) with the objective clinical assessment of range of motion (ROM) and strength (65% of the total score).…”
Section: American Shoulder and Elbow Surgeons Questionnaire (Ases) 11mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The Upper Extremity Functional Index (UEFI) is a patient-reported outcome measure (PROM) for quantifying UE function 3 that has been used in several studies of people with musculoskeletal UE problems. [4][5][6][7][8] Recently, we performed a Rasch analysis of the tool that informed its modification to a 15-item interval-level PROM (UEFI-15). 9 Psychometric properties of the UEFI-15 have not been compared to the original version, nor has the positive minimal clinically important difference (pMCID) been determined for either measure.…”
Section: Ré Sumémentioning
confidence: 99%
“…Therefore, a method such as SF-36, used to evaluate general daily life activity, was not used in the present study. A study comparing the Rotator Cuff-Quality of Life (RC-QOL) with WORC index as well as with other scales indicated that both forms were quite sensitive in determining alterations in patients with rotator cuff lesions (24). Holtby et al (25) compared the ConstantMurley Form, American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES), and WORC Index Form for evaluating patients with shoulder pain and they reported a strong correlation between them.…”
Section: Discussionmentioning
confidence: 99%